Orientation System Using Augmented Reality for Universities - Ortiz-Martinez, Elkin-Faber; Benavides-Zúñiga, David-Armando; Amador-Donado, Siler; Marceles-Villalba, Katerine; Camacho-Ojeda, Marta-Cecilia (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Augmented reality has been used in a variety of applications, including navigation, gaming, education, among others. This technology allows users to superimpose computer generated images on top of the real world environment. This article explores the potential of augmented reality to improve the orienteering experience for people unfamiliar with their surroundings. It describes how technology could be used to provide information and indications in the form of visual signals through the smartphone camera on the spaces of the Colegio Mayor del Cauca University Institution. In this way, students are provided with a tool to promote adequate compliance with the academic calendar and increase the adaptability of first-year students or the beginning of the semester. For the development of this idea, an experimental methodology is used to create and test a protot Augmented reality has been applied to different fields including navigation, gaming, and education. This technology allows users to superimpose computer generated images on top of the real-world environment. This article explores the potential of augmented reality to improve the orientation experience for people unfamiliar with their surroundings. It describes how technology could be used to provide information and indications in the form of visual signals through the smartphone camera in the facilities of the Colegio Mayor del Cauca University Institution. In this way, first-year students are provided with a tool to increase the adaptability and, in general, to promote compliance with the academic calendar at the beginning of the semester. To develop this idea, an experimental methodology is used to create and test a prototype with potential users. The results show that the use of augmented reality can help people to find their way more easily without incurring interruptions of academic activities. ype with potential users. The results show that the use of augmented reality can help people to find their way more easily without incurring interruptions of academic activities.